Информационная технология синтеза и анализа функциональных моделей интерактивных регламентов - Тимофеев, Владимир Александрович; Гуца, Олег Николаевич; Щербина, Екатерина Александровна (НТУ "ХПИ", 2016)
Рассмотрена информационная технология, которая преобразует знания ведущих специалистов организации в функциональную модель регламента (оптимального бизнес-процесса) на основе языка моделирования бизнес-процессов BPMN, а так же обеспечивает эксплуатацию созданной модели в интерактивном (on-line) режиме. На примере регламента аптечного провизора по обслуживанию клиентов показаны этапы реализации рассматриваемой информационной технологии и особенности отображения информации для пользователя в интерактивном режиме.

A person has no ability to capture entirely and to estimate correctly the logical coherence and consistency of Regulations in the Text Form. It leads to mistakes in a work of an Enterprise Staff and to impossibility of mastering of the Regulations with considerable volume. Presented Information Technology allows the Regulations Executor to receive on-line proper information of the Optimum Actions in any possible Situation, which can arise in the course of the work. Leading Experts of any Enterprise may create the full-fledged Expert System by themselves with the help of Specialized Software. Such a System will contain the knowledge in the Functional Model of Regulations (the Optimum Business Process). Stages of realization of the represented Information Technology and the peculiarities of on-line data displaying for the Regulations Executor are illustrated by the Pharmacy Customer Service Regulations.
The synthesis and analysis Information Technology of Interactive Regulations Functional Models
Keywords: BPMN; DSL; база знаний; бизнес-процесс; система экспертная; моделирование визуальное; язык моделирования; business process; expert system; knowledge base; visual modeling; modeling language